Pengaruh Penjualan Dan Biaya Operasional Terhadap Laba Bersih Pada Perusahaan Kosmetik Yang Terdaftar Di Bursa Efek Indonesia Periode Tahun 2019-2024 - Defi septiani, Defi septiani; Darwin Warisi; Meita Sekar Sari (CV. ULIL ALBAB CORP, 2025)
This study aims to analyze the effect of sales and operating expenses on net income in cosmetic companies listed on the Indonesia Stock Exchange (IDX) for the period 2019–2024. The data were obtained from the annual financial reports of cosmetic companies published on the IDX. The research method used is quantitative with multiple linear regression analysis conducted using SPSS version 29. The results show that partially, sales have a significant effect on net income with a significance value of 0.004 (< 0.05). Meanwhile, operating expenses do not have a significant effect on net income with a significance value of 0.086 (> 0.05). Simultaneously, sales and operating expenses have a significant effect on net income with a significance value of 0.001 (< 0.05). In conclusion, net income in cosmetic companies is more dominantly influenced by sales growth, while operating expenses need to be managed efficiently so as not to suppress profitability.